Discovery of a second species of Aesalini from Taiwan, with description of the new species of the genus Echinoaesalus Zelenka, 1993 (Coleoptera: Lucanidae) - Huang, Hao; Chen, Chang-Chin (Zootaxa, 2015)
Echinoaesalus chungi Huang & Chen, new species is described from Pingtung, Taiwan. It is the second species of the tribe Aesalini known from Taiwan. This new species is similar to the Bornean species Echinoaesalus arayai Huang & Imura, 2011, but can be distinguished mainly by the smaller size of the entire body, the laterally hooked sulcus on mentum of male, the separated sulci on mentum of female, the bristles inserted anteriorly in the wall of the punctures on dorsal surface of the body, the 9th abdominal segment of male with relatively larger paired pleurites, the medial lobe of parameres with weakly pigmented dorsal surface on distal half and with the pigmented distal sclerite interrupted on dorsal surface, and female genitalia with longer styli, thinner hemisternites and shorter bursa copulatrix. A key to the males of Echinoaesalus species is given. Female genitalia are described in detail for the new species and Echinoaesalus arayai.